Control of cell cycle progression by phosphorylation of cyclin-dependent kinase (CDK) substrates. Issue 4 (17th March 2010) - Suryadinata, Randy; Sadowski, Martin; Sarcevic, Boris
Abstract : The eukaryotic cell cycle is a fundamental evolutionarily conserved process that regulates cell division from simple unicellular organisms, such as yeast, through to higher multicellular organisms, such as humans. The cell cycle comprises several phases, including the S-phase (DNA synthesis phase) and M-phase (mitotic phase). During S-phase, the genetic material is replicated, and is then segregated into two identical daughter cells following mitotic M-phase and cytokinesis. The S- and M-phases are separated by two gap phases (G1 and G2 ) that govern the readiness of cells to enter S- or M-phase. Genetic and biochemical studies demonstrate that cell division in eukaryotes is mediated by CDKs (cyclin-dependent kinases). Active CDKs comprise a protein kinase subunit whose catalytic activity is dependent on association with a regulatory cyclin subunit. Cell-cycle-stage-dependent accumulation and proteolytic degradation of different cyclin subunits regulates their association with CDKs to control different stages of cell division. CDKs promote cell cycle progression by phosphorylating critical downstream substrates to alter their activity. Here, we will review some of the well-characterized CDK substrates to provide mechanistic insights into how these kinases control different stages of cell division.